The Influence of Education Funding Sources, Gratitude, and Organizational Participation on Students' Subjective Well-being - Ali Daud Hasibuan (Universitas PGRI Yogyakarta, 2026)
This study aims to analyze the effect of tuition fee sources, gratitude, and organizational participation on the subjective well-being of students at the Faculty of Tarbiyah and Teacher Training, State Islamic University of North Sumatra. A quantitative correlational design was employed with multistage proportional random sampling, involving 374 students selected from a total population of 5,837. Data were collected using Likert-scale questionnaires developed based on theoretical indicators for each variable, and the data were analyzed using multiple linear regression. The results revealed that simultaneously, tuition fee sources, gratitude, and organizational participation had a significant effect on students' subjective well-being (R² = 0.294; F = 51.310; p < 0.001). Partially, sources of tuition fees affected subjective well-being (β = 0.187; p < 0.001). Gratitude was the strongest predictor (β = 0.500; p < 0.001), and organizational participation also showed a significant but smaller effect (β = 0.086; p = 0.020). Students demonstrated high levels of gratitude, organizational activity, and subjective well-being across all tuition fee source categories, with empirical means exceeding hypothetical means. These findings confirm that enhancing students' subjective well-being requires adequate financial support, strengthening positive psychological attitudes through gratitude, and facilitating meaningful social involvement in organizational activities. The study contributes empirical evidence for developing comprehensive guidance and counseling programs in higher education that integrate financial assistance strategies, gratitude-based psychological interventions, and structured organizational engagement to support student well-being and academic success. Keywords: subjective well-being, gratitude, tuition fee sources, organizational participation, higher education students